Australia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Australia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This 2019 Article IV Consultation with Australia discusses that a continued gradual economic recovery is expected, subject to downside risks. Growth should continue to recover in 2020, but it will take time for the economy to return to potential and restore inflation to within the target range. Despite sound macroeconomic fundamentals and policy management, growth remains below potential and inflation is slightly below its target range. Growth is projected to recover gradually in the near term, supported by monetary policy easing, tax cuts, and the recovery of housing markets. Nonetheless, inflation is forecast to remain slightly below the target range until 2021 due to persistent economic slack. Downside risks, including a renewed escalation of the China-US tensions and weaker private consumption, remain elevated and have increased recently due to the widespread bushfires and the coronavirus outbreak. On the upside, looser financial conditions could re-accelerate asset-price inflation, boosting private consumption but also adding to medium-term vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet